X linked spondyloepiphyseal dysplasia: a clinical, radiological, and molecular study of a large kindred. Issue 10 (October 1996) - MacKenzie, J J; Fitzpatrick, J; Babyn, P; Ferrero, G B; Ballabio, A; Billingsley, G; Bulman, D E; Strasberg, P; Ray, P N; Costa, T
Abstract : X linked spondyloepiphyseal dysplasia (SEDT) is a rare disorder characterised by disproportionate short stature and degenerative changes in the spine and hips. We report a large kindred with 11 affected males and 17 obligate carrier females. We examined clinically and radiographically the seven living affected males and obtained detailed historical information on the four dead. The natural history was characterised by normal growth until late childhood. Decreased growth velocity was the earliest detectable abnormality. In adulthood, four subjects required hip replacements but disability was minimal. Clinical examinations showed a characteristic habitus with short stature (> 2 SD below the mean) and a decreased upper segment to lower segment ratio (> 1 SD below the mean) in all affected subjects. Also noted were scoliosis (6/7), and decreased range of hip rotation (6/7), and decreased range of movement of the lumbar spine (4/7). Radiographic evaluations were available on nine subjects. Radiographic changes were evident in two patients in childhood; findings in adulthood included narrow disc spaces (8/9), platyspondyly (7/9), the characteristic central and posterior hump of the vertebral bodies (6/9), bony spurs (7/ 8), and pelvic abnormalities (7/9). We also systematically evaluated eight obligate carrier females. They could not be distinguished from the general population on clinical and radiographic findings. Linkage analysis showed significant linkage with markers on Xp22, as previously reported. A recombinant event between DXS43 and DXS207 places the locus distal to DXS43.